The evaluation index improvement for the relocation of research equipment - Donghun Yoon (European Journal of Government and Economics (EJGE), 2019)
In this paper, evaluation index improvement for research equipment relocation is presented and discussed to boost the effectiveness of research equipment management. The analytic hierarchy process (AHP) model was designed for the evaluation index improvement for research equipment relocation, and the pairwise comparison scale was set up based on the importance of each evaluation criterion. The consistency rate (CR) was measured, and it was confirmed that the decision-making was reasonable. The improvement of the evaluation index was necessary for the objective and fair relocation of research equipment. Therefore, the evaluation index for the relocation of research equipment was designed for an objective and fair evaluation. It is hoped that the study findings will be very useful and will contribute greatly to the professors, researchers, and policymakers involved in science and technology policymaking and R&D.
Keywords: H11; H61; M10; M15; M21; 330; policy research; evaluation index; research equipment; science and technology; relocation